Distribuţia riscurilor în societatea românească şi efectele sale asupra politicilor de protecţie socială - Bădescu, Ciprian Ilie (Calitatea Vieții, 2012)
There has been a long debate within the government as well as the opposition circles about the social assistance system, its reform, risks and vulnerabilities and the accumulation of poverty and weaknesses within the Romanian population, implying a systematic examination of the whole package of these issues. We will try to give a description of such problems, and to verify the relationship between social risks, poverty, weaknesses, on the one hand, and policy responses, on the other hand.